Conformational changes induced in the envelope glycoproteins of the human and simian immunodeficiency viruses by soluble receptor binding. - Sattentau, Q J (1993)
We have investigated the molecular basis of biological differences observed among cell line-adapted isolates of the human immunodeficiency virus types 1 and 2 (HIV-1 and HIV-2) and the simian immunodeficiency virus (SIV) in response to receptor binding by using a soluble form of CD4 (sCD4) as a receptor mimic. We find that sCD4 binds to the envelope glycoproteins of all of the HIV-1 isolates tested with affinities within a threefold range, whereas those of the HIV-2 and SIV isolates have relative affinities for sCD4 two- to eightfold lower than those of HIV-1. Treatment of infected cells with sCD4 induced the dissociation of gp120 from gp41 and increased the exposure of a cryptic gp41 epitope on all of the HIV-1 isolates. By contrast, neither dissociation of the outer envelope glycoprotein nor increased exposure of the transmembrane glycoprotein was observed when sCD4 bound to HIV-2- or SIV-infected cells. Moreover, immunoprecipitation with sCD4 resulted in the coprecipitation of the surface and transmembrane glycoproteins from virions of the HIV-2 and SIV isolates, whereas the surface envelope glycoprotein alone was precipitated from HIV-1. However, treatment of HIV-1-, HIV-2-, and SIV-infected cells with sCD4 did result in an increase in exposure of their V2 and V3 loops, as detected by enhanced antibody reactivity. This demonstrates that receptor binding to the outer envelope glycoprotein induces certain conformational changes which are common to all of these viruses and others which are restricted to cell line-passaged isolates of HIV-1.